Being a team player: Approaching team coordination in sports in dialog with ecological and praxeological approaches - Thonhauser, Gerhard (Frontiers in Psychology, 2022)
This paper discusses key conceptual resources for an understanding of coordination processes in team sports. It begins by exploring the action guidance provided by the environment, studied in terms of affordances. When conceptualizing sporting performances in general, we might distinguish social and object affordances, think about the spatial and temporal order of affordances in terms of nested and sequential affordances, and differentiate between global, main, and micro affordances within an action sequence. In the context of team sports, it is crucial to understand how affordances might be given to a plurality of athletes. For that purpose, the paper defines shared, common, and collective affordances. A distinguishing characteristic of team sports is the key role of collaborative intra-team coordination which take place within a setting of antagonistic team-team interactions. A key proposal from dynamical systems theory is to conceptualize intra-team coordination in terms of synergies. Synergies are emergent systems of several athletes who coordinate their movements to achieve specific performance tasks. Many of the embodied skills that players need to develop to become suitable participants in the coordination processes of sport teams are abilities to participate in dynamic sequences of collective activity. Praxeological approaches have emphasized that training processes in team sports are aimed at transforming athletes into skillful participants in sequences of collective play. Athletes need to develop their ability-to-play-with to become proficient in contributing to the formation of suitable collectives for specific performance tasks.